2016
DOI: 10.1016/j.physletb.2016.06.053
|View full text |Cite
|
Sign up to set email alerts
|

Plateau inflation in SUGRA-MSSM

Abstract: We explored a Higgs inflationary scenario in the SUGRA embedding of the MSSM in Einstein frame where the inflaton is contained in the SU(2)SU(2) Higgs doublet. We include all higher order non-renormalizable terms to the MSSM superpotential and an appropriate Kähler potential which can provide slow-roll inflaton potential in the D-flat direction. In this model, a plateau-like inflation potential can be obtained if the imaginary part of the neutral Higgs acts as the inflaton. The inflationary predictions of this… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…In the early universe the no-scale Kähler potential gives the plateau inflation from supergravity (SUGRA) [6,7,9,63,64] which fits the requirements of the observed low tensor-to-scalar ratio and the temperature anisotropy. We consider the most economical SUSY model, namely the MSSM but allow R-parity violation.…”
Section: The Modelmentioning
confidence: 53%
See 2 more Smart Citations
“…In the early universe the no-scale Kähler potential gives the plateau inflation from supergravity (SUGRA) [6,7,9,63,64] which fits the requirements of the observed low tensor-to-scalar ratio and the temperature anisotropy. We consider the most economical SUSY model, namely the MSSM but allow R-parity violation.…”
Section: The Modelmentioning
confidence: 53%
“…Plateau inflation in MSSM with a D-flat combination of Higgs fields has been studied in [9]. In this paper we show that plateau inflation can be achieved in the Rparity violating MSSM where the TeV scale sneutrino and charged slepton masses can give testable LHC prediction like a diphoton resonance with significant cross section (σ pp→φ→γγ ∼ 10 fb).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The potential in NMSSM however has a tachyonic instability in the direction orthogonal to the slow-roll [108]. This instability can be cured by the addition of quartic terms of the fields in the Kähler potential [109,110] (see also [111]). In the context of a SUGRA embedding of the Starobinsky model, it was shown that quadratic Ricci curvature terms can be derived in SUGRA by adding two chiral superfields in the minimal SUGRA [112].…”
Section: Power Law Starobinsky Model From No-scale Sugramentioning
confidence: 99%
“…The family is parameterised by two real parameters, 1 This should not be confused with plateau inflation in Ref. [9].…”
Section: Introductionmentioning
confidence: 99%